Students’ mathematical literacy skill in term of gender differences: A comparative study - Edy Suprapto; Nunuk Suryani; Siswandari Siswandari; Mardiyana Mardiyana (International Journal of Evaluation and Research in Education (IJERE), 2023)
The emergence of the 21st century requires the younger generation to be able to face increasingly fierce global competition. One of the skills needed by the younger generation in this century is mathematical literacy. This ability needs to be improved in learning at school. One important factor that must be considered in learning mathematics literacy is gender differences. Therefore, this study aims to identify students' literacy abilities and find out the differences between male and female students at Madiun State Middle School. This research uses a quantitative approach in the form of a comparative study. The research sample of 336 students was analyzed using descriptive analysis and the Mann-Whitney test. The results of the study concluded that the ability of female students’ mathematical literacy was much higher than that of male students. Female students excel in terms of representation, modeling, mathematical communication, and problem posing and solving skills. Meanwhile, male students excel in terms of using math symbols and mathematical thinking and reasoning.